2016
DOI: 10.1371/journal.ppat.1005477
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Mediates Brain Microvascular Dysfunction Leading to Long-Term Cognitive Impairment in a Model of Experimental Cerebral Malaria

Abstract: Plasmodium falciparum infection causes a wide spectrum of diseases, including cerebral malaria, a potentially life-threatening encephalopathy. Vasculopathy is thought to contribute to cerebral malaria pathogenesis. The vasoactive compound endothelin-1, a key participant in many inflammatory processes, likely mediates vascular and cognitive dysfunctions in cerebral malaria. We previously demonstrated that C57BL6 mice infected with P. berghei ANKA, our fatal experimental cerebral malaria model, sustained memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
1
15
1
2
Order By: Relevance
“…This study had several limitations. First, as the study duration was shorter than that of other reports,12,5456 the present findings only indicate that IGF-1 may protect from learning and memory impairment caused by sepsis. Further studies of longer duration (1 month or even longer) should be performed to evaluate the effect of IGF-1 on long-term cognition, as long-term cognitive impairment is common in patients recovering from sepsis.…”
Section: Discussioncontrasting
confidence: 67%
“…This study had several limitations. First, as the study duration was shorter than that of other reports,12,5456 the present findings only indicate that IGF-1 may protect from learning and memory impairment caused by sepsis. Further studies of longer duration (1 month or even longer) should be performed to evaluate the effect of IGF-1 on long-term cognition, as long-term cognitive impairment is common in patients recovering from sepsis.…”
Section: Discussioncontrasting
confidence: 67%
“…In a recent publication, we demonstrated that treatment of PbA-infected mice with endothelin receptor A blockers preserved vascular integrity, prevented leukocyte infiltration, greatly mitigated long-term memory loss, and subsequently improved survival in mice with ECM. 75 Microvascular alterations are a hallmark of CM, yet there are currently no therapeutic strategies targeting these vascular complications in clinical settings. This study suggests that exploration of therapeutics aimed at targeting the ET-1 signaling cascade is warranted, as they may prevent both vascular and cognitive deficits in patients with CM.…”
Section: Et-1 Induces Murine Cerebral Malariamentioning
confidence: 99%
“…Endothelin family peptide ET-1 (Pre-proendothelin) also plays an important role in inducing BBB damage and produces a CM-like picture in rodent models [ 113 ]. Selective endothelin receptor antagonists also improved outcome in cognitive decline and decreased brain hemorrhages in mice [ 113 115 ].…”
Section: Introductionmentioning
confidence: 99%